Ceuta and Melilla Fences: A defensive System? - Cimadomo, Guido; Martínez Ponce, Pilar (Center for the Study of Development Societies (CSDS), 2006)
we want to focus on the alarming question of the assaults to Ceuta and Melilla’s fences, that occurred with a heightened frequency and strength during October 2005. They could be identified in the migratory asset, in a bigger movement of people without possibilities that cross the African continent, leaving their home in the hope of finding a better future in Europe. We want to show the actual situation as slow and misunderstood, as is the solution proposed for Spain: the militarization of border control (temporary?) and increasing the height of the fence from 3 to 6 meters where necessary, apart from the building of a third fence. These assaults demonstrate how the problem of immigration is not of each state on their own, but rather of the EU in general, as the adoption of Schengen Agreements allowed for free movements between member states. The solutions that are being proposed show more and more how the interests of the EU lay in strenghtening border control, with military forces if necessary, and in the politics of readmission with origin countries. We want to question the interaction of these migratory flows with the fences: of course the long way to reach Europe has many stops, dangers to avoid and ways to be walked, but it is in the arrival to the frontier with the EU we want to focus on. The fence is a permeable membrane according to the genre of flows it has to filter, but in the case of migratory ones it becomes a dense wall. We could say it generates an opposite vector force against the natural flow of migrants, whose only chance is to settle nearby while attempting to cross.
Keywords: Fronteras; Emigración e inmigración; Border; Borderland transformation; Migratory flows